Biomorphogenic Feedbacks and the Spatial Organization of a Dominant Grass Steer Dune Development - Bonte, Dries; Batsleer, Femke; Provoost, Sam; Reijers, Valérie; Vandegehuchte, Martijn L.; Van De Walle, Ruben; Dan, Sebastian; Matheve, Hans; Rauwoens, Pieter; Strypsteen, Glenn; Suzuki, Tomohiro; Verwaest, Toon; et al. (Frontiers in Ecology and Evolution, 2021)
Nature-based solutions to mitigate the impact of future climate change depend on restoring biological diversity and natural processes. Coastal foredunes represent the most important natural flood barriers along coastlines worldwide, but their area has been squeezed dramatically because of a continuing urbanisation of coastlines, especially in Europe. Dune development is steered by the development of vegetation in interaction with sand fluxes from the beach. Marram grass (Calamagrostis arenaria, formerly Ammophila arenaria) is the main dune building species along most European coasts, but also in other continents where the species was introduced. Engineering of coastal dunes, for instance by building dunes in front of dikes, needs to be based on a solid understanding of the species’ interactions with the environment. Only quantitative approaches enable the further development of mechanistic models and coastal management strategies that encapsulate these biomorphogenic interactions. We here provide a quantitative review of the main biotic and physical interactions that affect marram grass performance, their interactions with sand fluxes and how they eventually shape dune development. Our review highlights that the species’ spatial organisation is central to dune development. We further demonstrate this importance by means of remote sensing and a mechanistic model and provide an outlook for further research on the use of coastal dunes as a nature-based solution for coastal protection.